2017
DOI: 10.1590/2179-10742017v16i1890
|View full text |Cite
|
Sign up to set email alerts
|

Non-resonant Permittivity Measurement Methods

Abstract: Abstract- [7]. The purpose of this work is to generate explicit equations for the permittivity using a straightforward scattering parameters model for load-terminated samples. II. PERMITTIVITY MEASUREMENT METHODS A. Historical DevelopmentIn 1946, Roberts and Von Hippel [8] presented a method for the measurement of permittivity using an air-filled rectangular waveguide with a sample of MUT in the end of the waveguide. By

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
(25 reference statements)
0
16
0
3
Order By: Relevance
“…Основная идея метода заключается в измерении комплексных коэффициентов передачи (S 21 ) и отражения (S 11 ) при прохождении тестового сигнала через закрытую линию передачи (Рис. 2) без образца исследуемого материала и с образцом [4,5,6,7,8,9,10,11,12]…”
Section: нерезонансный методunclassified
“…Основная идея метода заключается в измерении комплексных коэффициентов передачи (S 21 ) и отражения (S 11 ) при прохождении тестового сигнала через закрытую линию передачи (Рис. 2) без образца исследуемого материала и с образцом [4,5,6,7,8,9,10,11,12]…”
Section: нерезонансный методunclassified
“…Considering the frequency range [2][3][4][5][6][7][8][9][10][11][12] GHz from Fig 9 and using a single or/and transmission line as well as two transmission line techniques with and without correction, terminated by an open-circuit configuration, it is clearly observed that the developed method using equation ( 18) is more suitable in comparison to those transmission line techniques as illustrated in Fig 10. The two transmission-line techniques yielded results with incertitude or a relative error of 3-7%, depending on the frequency used [15].…”
Section: Fig 9 Different Open-terminated Transmission-line Technique Principles Comparisonmentioning
confidence: 99%
“…The distributed element technique, using iterative method [2] and/or transmission-line propagation constant [3]- [5], is a well-known technique. As methods can be destructive or not [6], researchers are in the habit of using the transmission structure in short-circuit [7] and/or open-circuit [8] configurations along with reflection/transmission [9] in order to get to the material intrinsic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Other material techniques are investigated in several laboratories to better understand the different material properties and behaviors [2,4,5]. From microwave theory, material characterization methods can be categorized into two forms: non-resonant [6] and resonant processes [7], which can also be subdivided into two techniques, namely through one port technique [8] and two ports technique [9][10][11]. Among several existing methods [12,13], the probe or applicator method is well known [14][15][16].…”
Section: Introductionmentioning
confidence: 99%